2022
DOI: 10.1021/acsaem.2c02946
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Cost-Effective Synthesis of MgB2 for Energetic Applications

Abstract: In this paper, we report the low-temperature synthesis of MgB2 particles with improved ignition, high energy release, controlled particle size distribution, and minimum agglomeration. A facile solid-state reaction involving homogeneously mixed Mg (800 nm) and low-cost boric acid is used for the synthesis. X-ray diffraction patterns and high-angle annular dark-field–scanning transmission electron microscopy–energy-dispersive spectroscopy (HAADF-STEM-EDS) micrographs confirm the formation of MgB2, distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…After maintaining the isotherm, the furnace was turned off and venting was done for 2 h to cool the sample and bring it to room temperature. The schematic of this annealing process is shown in our previous works. ,,, Working conditions were designed by studying the phase diagram of the Al–B system . Al/B MM prepared above is the parent material to synthesize Al boride under different time and temperature conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After maintaining the isotherm, the furnace was turned off and venting was done for 2 h to cool the sample and bring it to room temperature. The schematic of this annealing process is shown in our previous works. ,,, Working conditions were designed by studying the phase diagram of the Al–B system . Al/B MM prepared above is the parent material to synthesize Al boride under different time and temperature conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Several methods have been studied to minimize the problems associated with the presence of native oxide on the B surface. Reducing the oxide layer without further passivation can cause explosions during storage and handling and is an unsafe practice. ,, Surface functionalization methods have been proposed to replace the oxide shell with organic polymers, metals and their hydrides, and fluorinated compounds to modify the oxidation performance of energetic materials, such as Al and B. The methods include high-temperature sintering of more reactive metals (Mg and Al) with B, mechanochemical methods such as reactive milling to form borides and coat B with other compounds such as hydrocarbons, and solution-based methods to coat the surface with fluorinated compounds and metals. Common limitations of these methods include: (a) high temperature causes sintering and agglomeration of B NPs due to melting of its oxide, which clogs the surface and blocks oxygen diffusion, (b) low reactivity and heat release due to the use of micrometer and bigger sized particles, and (c) the use of multiple chemicals and processing steps prone to introducing contaminants and are time-consuming.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the solid state the complete reduction of B 2 O 3 will be inhibited by slow diffusion processes, and hence it is likely that Mg and Al will form mixed oxide phases with B on reacting with B 2 O 3 . Recent studies on the energetic performance of Al/B and Mg/B composites prepared through ball-milling, plasma deposition, or physical mixing have reported an ∼30–60% enhancement (Figure (a)) in the reactivity of B on addition of Al and Mg as minor components. The percent enhancement presented in Figure (a) is obtained from calorimetry, pressurization rate, burn time, or ignition delay measurements. In one of these studies, the highest enhancement in reactivity, ∼60%, has been reported for a 10 wt % Mg/B physically mixed nanoparticulate system .…”
Section: Introductionmentioning
confidence: 99%
“…Surface functionalization of Al NPs is an effective pathway to minimize the adverse effects of native oxides on their energetic performance. Several studies focus on eliminating the native metal oxides during oxidation through exothermic chemical reactions, extracting energy from nonenergetic oxide. The elimination of the surface oxide serves two purposes. First, it maximizes the contact of metal and oxidizer by reducing the diffusion barrier, leading to more complete oxidation of the core metal and enhancing the overall energy release from the material. Second, it reduces the percentage of dead mass, thereby increasing the active metal content in the sample. One approach to eliminate native oxide is based on surface functionalization with species that can react exothermally with the oxide during thermal oxidation. The reactive coatings formed from energetic components (Fe, Ni, nitrocellulose, and fluorocarbons) react with the oxide via exothermic thermite and fluorination reactions to eliminate the surface barrier. These exothermic surface reactions form channels that promote metal/oxidizer reactions, which contribute to the overall oxidative energy release. Most of the studies in the literature are based on wet chemistry, which is time-consuming due to the additional steps of drying and separation, causes contamination, and is performed on bigger-sized particles such as μ-Al. ,, These methods improve energy release from Al particles, but the overall energy release is less than 40% of Al’s th...…”
mentioning
confidence: 99%